Correction: Contexts for developing of national essential diagnostics lists. Lessons from a mixed-methods study of existing documents, stakeholders and decision making on tier-specific essential in-vitro diagnostics in African countries. - PLOS Global Public Health Staff (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pgph.0001893.].